2018
DOI: 10.1051/matecconf/201817203005
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue life prediction under mixed-mode loading using equivalent stress intensity factor models

Abstract: Damage tolerance principles are widely used to assess the structural integrity and failure of engineering components. The advances in numerical simulation techniques facilitate the prediction of fatigue life of engineering component, which is essential in damage tolerance design. For the components under mixed mode (I/II) loading, the fatigue crack growth and life is predicted by using a modified form of Paris' law along with the equivalent stress intensity factor (ΔKeq). Numerous ΔKeq models are available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Figure 6A shows the crack paths of the fatigue tests relative to the loading angles of 30 and 60 predicted by the proposed method and Sajith et al, 24,66 whereas Figure 6B compares the number of remeshing events as a T A B L E 1 Material properties of the plate and loading angles and loading levels assumed in the present study.…”
Section: Case 1: the Fatigue Behavior Of A Cts Steel Specimenmentioning
confidence: 86%
See 2 more Smart Citations
“…Figure 6A shows the crack paths of the fatigue tests relative to the loading angles of 30 and 60 predicted by the proposed method and Sajith et al, 24,66 whereas Figure 6B compares the number of remeshing events as a T A B L E 1 Material properties of the plate and loading angles and loading levels assumed in the present study.…”
Section: Case 1: the Fatigue Behavior Of A Cts Steel Specimenmentioning
confidence: 86%
“…In the present study, for conciseness, the fatigue behavior of the CTS steel specimen is analyzed for the cases of Φ ¼ 30 and Φ ¼ 60 only. In particular, according to Ma et al, 65 The predictions of the proposed method are compared with experimental and numerical results provided by Ma et al 65 and also with numeric previsions achieved by Sajith et al 24,66 and Cheng et al 67 Concerning numerical results, it is worth noting that Ma et al 65 and Sajith et al 24,66 have used standard FEbased numerical models, which update the computational mesh of the numerical model for each increment of the crack length during the propagation process. In particular, for the case of Φ ¼ 30 , Sajith et al 24 report that the crack propagation process has been conducted by extending the crack through incremental steps of size Δa ¼ 0:5 mm starting from the initial crack length of 45 mm to the final length of 65 mm.…”
Section: Case 1: the Fatigue Behavior Of A Cts Steel Specimenmentioning
confidence: 95%
See 1 more Smart Citation
“…A number of other equations for an equivalent mixed mode stress intensity factor found in literature have also been implemented. An overview and comparison of a number of these models can be found in [37]; a thorough review on mixed-mode fracture of metals can be found in [38]. The oscillating behaviour of the extracted SIF along the crack front can introduce difficulties when performing a FCG analysis; especially for a simulation that requires a large number of iterations.…”
Section: X-fem Data Extraction and Processingmentioning
confidence: 99%
“…where,  is geometrical coefficient, 𝜎 𝑡𝑖𝑝 maximal stress at the notch tip. In this test, the specimen is subjected to a mixed mode I and II due to a deviation of crack by a low angle in which mode I appears a predominant mode with higher values compared to mode-II, the stress intensity factor used is the equivalent notch stress intensity factor described by Irwin et al [26,27].…”
Section: Notch Stress Intensity Factors Expressionmentioning
confidence: 99%